Synthesis of ternary nanocomposites of GO–MnO2@Tau and GO-MnO2@CA for efficient removal of dyes: DOI: 10.48129/kjs.19959 - Bibi, Iram; Raza, Khalid; Rehman, Prof.Wajid; Begum, Siddiqa; H. Abdellatif , Magda; Muhammad, Saz; Hussain Shah, Waqar; A. Shah, Luqman; Bibi, saira; Khan, Wajiha (Kuwait Journal of Science, 2023)
Here, we report the facile route for the synthesis of graphene oxide–functionalized manganese dioxide (GO–MnO2@Tau (GMT) and GO-MnO2@CA) (GMC) nanohybrids and their use as adsorbents for removal of selected dyes from industrial effluents. These nanohybrids were also tested for antibacterial activity in wastewater. Manganese dioxide nanoparticles were synthesized by redox reaction between potassium permanganate (KMnO4) and manganese acetate (Mn(CH3COO)2.4H2O) and functionalized with taurine (H3N+CH2CH2SO3−) and caproic acid (CH3(CH2)8COOH) to produce MnO2@Tau and MnO2@CA. These functionalized-MnO2 were then exploited as reinforcement in graphene oxide (GO) to fabricate nanohybrids. The nanohybrids were characterized for their morphology, structure, crystallinity and thermal behavior by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infra-red (FTIR) spectroscopy, UV-Visible spectroscopy and thermogravimetric analysis (TGA). They were investigated for adsorptive removal of methylene blue and malachite green and effect of temperature and quantity of adsorbent were studied. The adsorption of both dyes followed pseudo first order kinetics. The antibacterial activity of GO-MnO2@Tau and GO-MnO2@CA nanohybrids were tested against two bacterial strains (Gram-negative E. coli, and the Gram-positive S. aureus) and the results revealed efficient inhibition of these pathogens.